Optimization of Marine Diesel Engine Performance Using ‎Advanced Stimulation Techniques - Rajesh , K.; Kumar, Krishnamurthy (International Journal of Basic and Applied Sciences, 2025)
Most ships, from small boats to huge oceangoing vessels, are diesel-powered, which are the most efficient engine. Thirty-four member ‎states are regulated by international environmental laws established by different global institutions and organizations, with the goal of ‎curbing greenhouse gas emissions. Optimization techniques are needed to lower marine engines' fuel consumption and exhaust pollutants. ‎Choosing the right combustion control settings is crucial for marine diesel engines because it allows for the simultaneous improvement of ‎efficiency and emissions while maintaining a steady target engine speed. Basing their discussion on their wide-ranging experience with ‎emission control systems, especially plasma aftertreatment systems, the authors offer a distinct view of marine diesel engines and ‎aftertreatment technologies in "New Technologies for Emission Control in Marine Diesel Engines". For oceangoing ships, the feasibility of ‎a load leveling approach and energy management optimization using a hybrid diesel propulsion system is examined. By using less fuel oil ‎and introducing an energy storage medium, diesel hybrid systems aim to lower exhaust gas pollutants.
Keywords: Optimization; Fuel Consumption; Propulsion System; Energy Management